Peran Pesantrenpreneur dalam Pemberdayaan Santri Pondok Pesantren Roudlotun Nafi’iyah - Ubaid Aisyul Hana; Suci Reza Syafira; Fauzan; Bagus Swi Endrayana (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2022)
This study aims to determine the strategies of Islamic boarding school caregivers in empowering students to have an entrepreneurial spirit. This research uses a qualitative approach with descriptive methods. Data collection techniques through interviews and observation. The result of this research is that Islamic boarding school education gives birth to students who have skills in all knowledge, both religious knowledge, technology science and entrepreneurship. This will have implications for unraveling the potential bottlenecks of pesantren as well as being one of the agents of change. The author can conclude: the application of pesantrenpreneurs at the Roudlotun Nafi'iyah Islamic Boarding School needs to be given continuous training in accordance with the field of business they are in. The obstacles that exist in the pesantrenpreneur at the Roudlotun Nafi'iyah Islamic Boarding School include the lack of ability to manage time when studying, reciting the Koran and working. _________________ Penelitian ini bertujuan untuk mengetahui strategi pengasuh pondok pesantern dalam memberdayakan para santri untuk memiliki jiwa wirausaha. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data melalui wawancara dan observasi. Hasil dari penelitian ini adalah pendidikan pesantren melahirkan sumber daya santri yang memiliki kecakapan dalam segala ilmu, baik ilmu agama, ilmu teknologi maupun ilmu kewirausahaan. Hal ini akan berimplikasi pada penguraian kemacetan potensi pesantren sekaligus sebagai salah satu agents of change. Penulis dapat menyimpulkan: penerapan pesantrenpreneur di Pondok Pesantren Roudlotun Nafi’iyah perlu diberikan pelatihan yang berkesinambungan sesuai dengan bidang usaha yang digelutinya. Kendala yang ada dalam pesantrenpreneur di Pondok Pesantren Roudlotun Nafi’iyah antara lain kurang bisa mengatur waktu saat kuliah, mengaji dan bekerja.